Minimalisasi Pelanggaran Lalu Lintas Melalui Sistem ETLE (Electronic Traffic Law Enfforcement) oleh Satlantas Polresta Banyumas - Ade Harsa Suryanegara (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Law enforcement in the field of traffic is part of the contribution to the realization of security, safety, order, and smoothness of traffic. This can be done by applying appropriate sanctions for traffic violations. Thus, information technology is needed to support enforcement and prevent deviant practices committed by unscrupulous police officers. One of the Industry 4.0 technology-based public service innovations in the traffic sector is the ETLE (Electronic Traffic Law Enforcement) system. ETLE is a law enforcement system in Indonesia related to traffic discipline and safety. This paper discusses the efforts of the Banyumas Police Traffic Unit in minimizing traffic violations through the ETLE system. The current problem of traffic violations still requires road user awareness. Thus, traffic violations can be minimized as best as possible. With the ETLE system organized by the Police Traffic Unit, traffic security and order can be created properly.